Self-esteem and numerical and reading comprehension in fourth grade students from a state educational institution - Guzmán Grados, Jaime Percy (2021)
A substantive-type study with a descriptive and correlational design, to determine the relationship between self-esteem and numerical and reading comprehension in students of the fourth grade of primary school of a state educational institution. The sample consisted of 86 schoolchildren: 38 women (44.2%) and 48 men (55.8%) from the El Agustino district in Metropolitan Lima. Three measurement instruments were used: the Coopersmith Self-Esteem Inventory, the Numerical Comprehension, and the Reading Comprehension Test for the Primary Level. The students present an Average Low level in self-esteem, and an Average performance in numerical comprehension and reading comprehension; a relationship between self-esteem and numerical comprehension was not found in the total sample (Rho = .142; p = .191), neither in men (Rho = .162; p = .272) nor in women (Rho = .107; p = .521). Nor was a relationship between self-esteem and reading comprehension found in the complete sample (Rho = .206; p = .057); but there are gender differences and in men the relationship is clear and highly significant (Rho = .432; p = .002), and for women it is practically non-existent (Rho = -.024; p = .884). A significant relationship was found between numerical comprehension and reading comprehension (Rho = .427; p< .001); very noticeable in men (r = .522; p< .001) and women (Rho = .453; p= .004). Men and women do not differ in self-esteem (p= .760), neither in numerical comprehension (p= .305) nor in reading comprehension (p= .093).